The Osteoclast Traces the Route to Bone Tumors and Metastases - Russo, Sharon; Scotto di Carlo, Federica; Gianfrancesco, Fernando (Frontiers in Cell and Developmental Biology, 2022)
Osteoclasts are highly specialized cells of the bone, with a unique apparatus responsible for resorption in the process of bone remodeling. They derive from the differentiation and fusion of hematopoietic precursors, committed to form mature osteoclasts in response to finely regulated stimuli produced by bone marrow-derived cells belonging to the stromal lineage. Despite a highly specific function confined to bone degradation, emerging evidence supports their relevant implication in bone tumors and metastases. In this review, we summarize the physiological role of osteoclasts, and then focus our attention on their involvement in skeletal tumors, both primary and metastatic. We highlight how the osteoclast-mediated bone erosion confers increased aggressiveness to primary tumors, even those with benign features. We also outline how breast and pancreas cancer cells promote osteoclastogenesis to fuel their metastatic process to the bone. Furthermore, we emphasize the role of osteoclasts in reactivating dormant cancer cells within the bone marrow niches for manifestation of overt metastases, even decades after homing of latent disseminated cells. Finally, we point out the importance of counteracting tumor progression and dissemination through pharmacological treatments based on a better understanding of the molecular mechanisms underlying osteoclast lytic activity and their recruitment from cancer cells.